"uniMatchUp!": An application for promoting academic help-seeking and group development - Lisa Ollesch; Jens Kohlmann; Maribell Steiner; Osman Tasdelen; Daniel Bodemer (FernUniversität Hagen, 2022)
This paper describes the conception, development, and evaluation of a peer support web application for university students. The main goal of uniMatchUp! is to help students in finding appropriate academic support and learning groups by providing Group Awareness (GA) information about various aspects of fellow students that are useful for online learning. The study contributes to a better understanding of the use of GA tools in the university context and reveals that active engagement with the application, in the form of contributed questions and answers, is positively associated with study satisfaction. During the interaction with uniMatchUp!, cognitive GA information (contribution quality) was considered more relevant than behavioral (amount of participation), and emotional (well-being) GA information about other students. The findings also provide potentials for improvement, which can shape the further development of uniMatchUp! and future applications.